Ecological Electroplating Baths and Their Application in the Tin-coating of Copper Wires Intended for Photovoltaic Cables - Olędzki, Aleksander; Knych, Tadeusz; Zasadzińska, Małgorzata (Journal of Casting & Materials Engineering, 2023)
Copper wires are covered with various coatings for many different applications. The most popular are tin based coatings and both their thickness and quality have been standardized by means of appropriate standard specifications. Copper wires intended for photovoltaic cables are subjected to especially high requirements due to their exceptionally long operating time and extremely unfavourable working conditions. Tin coatings are applied using the electroplating method and generally a fluoroborate bath is used during the process, however, it has been proved to be a health hazard in general and harmful to the environment as a whole. The paper presents the research results of a new ecological methane-sulfonate bath which does not form hazardous waste in the process. The examples of tin coatings of various thickness and the way of obtaining them at varying electrodeposition speeds at constant current or constant speed with varying current intensity were analysed. It has been determined that the use of the new electroplating bath is not only beneficial from an ecological point of view, but also in terms of the coating quality and efficiency of the process.